COMPARATIVE STUDY OF ETHOSOMES AND PHARMACOSOMES AS A PROMISING APPROACH FOR IMPROVING DAPSONE AND CLOXACILLINE TRANSDERMAL ANTI-LEPROTIC ACTIVITY: IN VITRO AND IN VIVO STUDIES - MAURYA, PRIYANKA; GUPTA, TAPASVI; GILHOTRA, RITU (International Journal of Applied Pharmaceutics, 2026)
Objective: This study aimed to develop and evaluate a vesicular gel system for the topical delivery of dapsone and cloxacillin with the goal of enhancing drug permeation, sustaining release within the skin, and improving wound healing efficacy. Methods: Gel were prepared and characterized for particle size, (PDI) Polydispersity index, zeta potential, and encapsulation efficiency. Optimized formulations F3 and P5 were further subjected to (FTIR) Fourier transform infrared spectroscopy, (SEM) Scanning electron microscopy, and (TEM) Transmission electron microscopy analyses to confirm FTIR and vesicle morphology. In vitro drug release of G3 and G5, skin irritation testing, stability studies, and in vivo wound healing evaluations were performed. Results: F3 and P5 showed favorable Nano scale vesicle characteristics (116.3 nm and 110.6 nm; PDI: 0.32 and 0.36; zeta potential: –21.7 mV and –30.6 mV; encapsulation efficiency: 71.91% and 73.95%). The gels G3 and G5 demonstrated desirable physicochemical properties (pH 7.0, high drug content of 76.88% and 83.54%, viscosity 45.223 cps and 40.154 cps, and superior spreadability). In vitro release studies confirmed biphasic sustained release, with G3 showing the highest cumulative release (88.68% over 24 h). Stability studies indicated no changes in physicochemical properties after 3 mo. Skin irritation tests confirmed biocompatibility, and in vivo experiments demonstrated superior wound healing with ethosomal gels, particularly G3, as evidenced by morphological and histological studies. Conclusion: The ethosomal gel system, especially G3, offers significant potential as a topical carrier for dapsone and cloxacilline, with enhanced penetration, sustained release, stability, safety, and superior wound healing efficacy compared to conventional formulations.